Managing contested spaces: public managers, obscured mechanisms and the legacy of the past in Northern Ireland - Murphy, Joanne; McDowell, Sara; Braniff, Marie; Denyer, David (SAGE, 2017)
Societies emerging from ethno-political and inter-communal conflict face a range of complex problems that stem directly from the recent lived experience of bloodshed and injury, militarisation, securitisation and segregation. As institutional agents in such an environment, public managers perform the dual role of both interpreting public policy and implementing it within a politically contested space and place. In this article we address how managers cope with the outworking of ethno-nationalist conflict and peace building within government processes and policy implementation and contend this is a subject of emerging concern within the wider public administration, urban studies and conflict literature. Using data from a witness seminar initiative on the Northern Ireland conflict transformation experience, we explain how public sector managers make sense of their role in post-agreement public management and highlight the importance of three identified mechanisms; ‘bricolage’, ‘diffusion’ and ‘translation’ in the management of public sector organisations and urban spaces in a context of entrenched conflict and an uncertain path to peace.
Keywords: Conflict transformation; urban management; public managers; bricolage; diffusion; translation; Northern Ireland